A kenetic approach for the determination of host-guest binding constants - Caleb E. Feliciano; Marieliz Garcia; Helena Rivera; Yasmin Pedrogo; Edwin Quiñones (ՀՀ ԳԱԱ հրատ.)
The kinetics of the alkaline hydrolysis of methyl acetate (E) was studied in the presence of β-cyclodextrin (CD), employing a conductance method.
Keywords: Biology; Biochemistry; Pharmacology